Пираты Елизаветы. Золотой век - Марвел Питер (Пираты Карибского моря, 2008)
Экземпляры: (20220406) / Инвентарный номер: 33438 / Цена: 273,02 / Сис.шифр: 84(4Вел) / Авт.знак: М 25 / ГРНТИ: 17 / ББК: 84(4Вел)